What treatments are effective for relieving blepharospasm (eyelid twitching)?. Issue 4 (April 2017) - O'Dowd, Stacy; Juan, Maria San
Abstract : EVIDENCE‐BASED ANSWER : Botulinum neurotoxin type A (BoNT‐A) is effective in up to 90% of patients with primary blepharospasm. IncobotulinumtoxinA (Xeomin®), a highly purified version of BoNT‐A, results in small further improvements in blepharospasm and functional impairment in patients who have already received BoNT‐A (SOR: B, RCTs). The addition of topical acetyl hexapeptide‐8 (AH8) is not more effective than BoNT‐A alone (SOR: B, RCT).